Disturbance effects on species diversity and functional diversity in riparian and upland plant communities - Shekhar R. Biswas; Azim U. Mallik (Ecology, 2010)
Understanding disturbance effects on species diversity and functional diversity is fundamental to conservation planning but remains elusive. We quantified species richness, diversity, and evenness and functional richness, diversity, and evenness of riparian and upland plants along 24 small streams subjected to a range of anthropogenic disturbances in the boreal forest of northwestern Ontario, Canada. We included a total of 36 functional traits related to productivity, competitive ability, reproduction, disturbance tolerance, life history, and tolerance to habitat instability. Using nested ANOVA, we examined the response of diversity indices to disturbance and whether it followed the intermediate disturbance hypothesis (IDH) and varied with habitat stability. We found that, like species richness and diversity, functional richness and diversity reached peaks at moderate disturbance intensity; functional diversity followed the predictions of the IDH. Second, disturbance–habitat‐stability coupling has very little effect on overall species and functional diversity, but the effect on particular life forms and functions may be significant. Since species richness and diversity patterns are context and system dependent, our findings should be most applicable to similar temperate riparian systems.